MACROPROLACTINEMIA WITH CO-EXISTING PITUITARY MACROADENOMA AS A DIFFERENTIAL FOR DOPAMINE-AGONIST RESISTANT PROLACTINOMA - Mohamad, Aimi Fadilah; Vethakkan, Shireene; Ratnasingam, Jeyakantha; Paramasivam, Sharmila; Lim, Lee-Ling (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Macroprolactinemia is a condition where there is assay interference resulting to a falsely elevated prolactin level. The interference is due to the presence of antibodies that form large complexes with existing prolactin. This condition is asymptomatic and has no direct effects on health. It may coincide with a non-functioning pituitary adenoma and may be mistaken for drug resistant prolactinoma. CASE We present a case of a 63-year-old female with chronic headaches for 2 years with blurred vision which necessitated imaging. There was a finding of pituitary macroadenoma (0.7 x 1.2 x 0.8 cm) on MRI Brain. Anterior pituitary hormone panel revealed hyperprolactinemia and hypogonadotrophic hypogonadism. Serum prolactin was 8510 miu/L (NR <500 miu/L), serum oestradiol <43 pmol/L, leutenizing hormone (LH) 0.1 miu/L (NR 2.4 – 12.6) and follicle-stimulating hormone (FSH) 3.2 miu/L (NR 3.5 – 12.5). Other pituitary hormones were normal. A diagnosis of prolactinoma was made. She was started on cabergoline initially at 0.25 mg twice weekly and dose increased according to serum prolactin response. She required cabergoline doses of 7 mg weekly to achieve normalization of serum prolactin. Serial MRI Pituitary showed no change in size of pituitary lesion despite treatment duration of >2 years. These are consistent with Dopamine-agonist resistant prolactinoma. Subsequently, PEG Precipitation analysis of serum prolactin was performed to assess for macroprolactinemia. This confirmed presence of macroprolactinemia with the percentage of PEG-precipitable prolactin being 64% (>60% is diagnostic). Cabergoline was stopped with subsequent monitoring of anterior pituitary hormones. CONCLUSION The diagnosis is Macroprolactinemia with co-existing non-functioning pituitary adenoma. The management is drastically different from a drug resistant Prolactinoma which requires surgical intervention. This highlights the importance of establishing the correct diagnosis and having a high index suspicion of assessing for macroprolactin.